ANALISIS PENGARUH FRAUD TRIANGLE TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI DENGAN SELF EFFICACY SEBAGAI VARIABEL MODERASI - Fachry Saldina, Moch (COMPETITIVE, 2021)
Education is a means to improve the quality of human resources. Education also has a major impact on physical, psychological, and moral development as well as all aspects of human life. Education is also one of the benchmarks for the progress of a country. Universities must of course be able to train highly qualified professionals in knowledge and ethics (Fitriana & Baridwan, 2012). Article 1 paragraph 2 of the Law of the Republic of Indonesia Number 12 of 2012 higher education is the level of education after secondary education, which includes diploma, bachelor, master, and doctoral education programs organized by universities/colleges. It is at the University/College that students will be given education and guided as experts based on the fields they master in lectures and are expected to produce the best graduates in academic and non-academic fields, especially in the formation of good character. Based on the type of data, this research includes research using quantitative methods. The results of the research Pressure, Opportunity, Rationalization, and Self-Efficacy have a positive effect on the occurrence of academic fraud. The results prove that there is a positive influence of Academic Pressure, Rationalization of cheating, and the need for cheating and all these effects are positively moderated by moderating variables namely Self-Efficacy against academic cheating behavior, therefore to reduce or minimize academic cheating behavior, it is necessary to control the factors that influence it.